Penerapan Metode Gross Up Dalam Penghitungan PPH Pasal 21 Studi Pada PT Fairfax Insurance Indonesia - Nurmaulida, Nurmaulida, Dra. Mujiyati M.Si (2016)
There are 3 methods of calculating income tax article 21, namely the net method, gross method, and gross up method. One of that can be applied is a gross up method. The purpose of this research is to analyze the application of the method of counting up in gross income tax article 21 PT Fairfax insurance Indonesia. This research is descriptive research using quantitative analysis. The results showed that use of the method of gross up would be profitable for both parties either companies or employees by granting tax benefits of PPh pasal 21 intersected on the income of employees. When using the net method, then the company must the PPh pasal 21 up employees of Rp 65,817,700 and non deductible expenses. When using the method of gross up clause 21 pph costs incurred amounted to Rp 130,095,754 is equal to the magnitude of the tax benefits provided by the company and the allowances given is tax-deductible expenses. Thus saving the corporate tax burden. Increased welfare for employees, with an increase in gross income, take home pay equals the net method and tax obligations are met. Key words: gross up method, the net method, gross method, PPh pasal 21.